1983
DOI: 10.1177/000331978303401107
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous and Arterial Thrombosis in Pregnancy and Puerperium: A Study of 135 Patients

Abstract: Cerebral venous thrombosis occurring in puerperium is about 10 to 12 times more frequent in India than in Western countries. A clinical study of 135 patients with cerebrovascular accidents in early puerperium is reported. Cortical vein thrombosis is common and arterial thrombosis rare (6/135). The illness usually occurs within the first two weeks, after normal delivery at full term, in a multiparous woman, with multi-focal seizures, stupor or coma, regressing focal signs or at times as pseudotumour cerebri. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
92
0
2

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 12 publications
11
92
0
2
Order By: Relevance
“…8,9 Mehta SR et al found seizures in 26.6%. In our study 26.4% of patients had convulsion of which generalized tonic clonic type was commonest.…”
Section: Discussionmentioning
confidence: 98%
“…8,9 Mehta SR et al found seizures in 26.6%. In our study 26.4% of patients had convulsion of which generalized tonic clonic type was commonest.…”
Section: Discussionmentioning
confidence: 98%
“…2 Srinivasan suggested that puerperal CVT is seen more frequent in India compared to western countries. 3 The reason for this high incidence is not clear. There have been many studies from India on postpartum CVT.…”
Section: Introductionmentioning
confidence: 99%
“…Srinivasan in his study stated that puerperal CVT was 10-12 times more frequent in India and the predisposing factors like anaemia, increased coagulability of blood, slowing of the blood stream and dehydration aggravated by the local custom of withholding fluid intake in puerperium contributed to the high incidence of CVT. 3 Alexander et al in their study stated that in patients with pregnancy associated CVT, prothrombotic markers can be multiple and are associated with increased odds of mortality. 4 In addition to these pathophysiologic processes and factors, several other risk factors have also been noted by various investigators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In occidental countries, CVT is an unusual complication of pregnancy with an incidence of 1:10,000 to 1:20,000 deliveries, mainly observed during the postpartum period, and represents the main cause of puerperium stroke.…”
mentioning
confidence: 99%